Post-truth and misleading narratives: consequences for Costa Rican democracy (2022-2024) - Hernández Arroyo, Wilson (2025)
Introduction: This essay explores the impact of post-truth and disinformation on Costa Rican democracy during the 2022-2024 period. It analyzes the false statements and misleading narratives of President Rodrigo Chaves and his team, focusing on how these distort public perception and affect democratic institutions. Objective: To analyze how disinformation emanating from the Executive Branch has influenced democratic stability and citizen participation, highlighting the different types of disinformation used. Method: A content analysis of the Costa Rican government's public statements, extracted from the national press, was carried out, organizing the falsehoods into categories according to their type (false content, misleading, false context, among others). Surveys and opinion studies were also consulted to contextualize the impact of these narratives. Results: The analysis reveals a deliberate pattern of disinformation used to influence public opinion. Despite the exposure of falsehoods, popular support for the president remained stable, reflecting the power of disinformation in solidifying political narratives. Conclusions: It is concluded that disinformation issued from high levels of government represents a significant challenge to Costa Rican democracy. Information literacy is crucial in combating this phenomenon, enabling citizens to make informed decisions and protect democratic integrity.